Hysteria [videorecording (DVD)] - Wexler, Tanya; Dancy, Hugh, 1975-; Gyllenhaal, Maggie, 1977-; Pryce, Jonathan; Jones, Felicity; Everett, Rupert (Sony Pictures Home Entertainment, 2012)
In 1880 London, a young doctor who sets out to find a medical cure for "hysteria" in women invents the electro-mechanical vibrator.